(untitled) (CIPEEX, 2025)
Introduction: Childhood obesity is considered a global epidemic by the WHO and represents a major risk factor for several chronic diseases. In this context, Primary Health Care plays a central role in developing preventive and health promotion actions, specifically nursing professionals. Objective: To review the literature on nursing roles in Primary Health Care focused on the prevention and management of childhood obesity. Methods: This is an integrative review conducted using the PICO strategy. Studies published in the last five years, with a cross-sectional design, and available in English were included. Searches were conducted in August 2025 in the PubMed, BVS, and SciELO databases. Descriptors combined with Boolean operators were used as follows: child AND obesity AND primary care AND nursing performance. Initially, 87 studies were identified, of which only 6 met the eligibility criteria and were included in the review. Results: The selected studies highlighted the nursing consultation as a strategic moment for establishing bonds between professionals, children, and families. This space proved crucial for defining comprehensive care strategies, enabling shared care focused on modifying the multifactorial factors that influence childhood obesity. Conclusion: Health education provided by nurses, with active family participation, has proven effective in combating childhood obesity and improving quality of life. However, its relevance remains underappreciated, highlighting the need for public policies to raise awareness and professional training.